Continuing Professional Development and teachers’ perceptions and practices - A tenable relationship - Utami, IGA Lokita Purnamika; Prestridge, Sarah; Saukah, Ali; Hamied, Fuad Abdul (Universitas Pendidikan Indonesia, 2019)
Research on the impacts of Continuing Professional Development (CPD) on perceptions and practices has been conducted separately. This study attempts to investigate a relationship between the involvement of CPD and the alignment of teachers’ perceptions and practices about effective English teaching to draw a critical link between the relationship and the alignment. This study involved 6 teachers of English as a Second Language in Indonesia. Qualitative approaches of in-depth interviews and observations were the primary data collection tools. The findings indicate a partial relationship between CPD involvement and the alignment of teacher’s perceptions and practices. Specifically, as part of CPD, teacher’s professional enthusiasm is an indicator for a closer alignment in teacher’s perceptions and practices. Implications drawn from this study suggest that greater conscious raising is required to enhance teachers’ professional enthusiasm since it leads to an alignment between perceptions and practices of quality teaching.